Frame-Semantic Approach in the Analysis of Handicraft Lexicon in Uzbek and English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This thesis explores the relevance of the frame-semantic approach in analyzing the lexicon of handicrafts in both Uzbek and English languages. The study demonstrates how frame semantics provides a deeper understanding of linguistic units not only as isolated meanings but as conceptual structures connected to cultural knowledge and worldview. By applying this approach, the research uncovers the linguacultural, cognitive, and etymological layers that reflect national identity and cultural heritage embedded in handicraft terminology.